Harnessing the Global Recovery : A Tough Road Ahead - Mottaghi, Lili (World Bank, Washington, DC, 2014)
Compared with the past three years, 2014 seems hopeful and 2015 can be a turning point for Middle East and North Africa (MENA) countries. After a slowdown in 2013, recovery in high income economies is expected to boost global growth to 3.2 percent in 2014, an increase of 0.8 percent from 2013. Global output is to improve further in 2015 with real gross domestic product (GDP) growth of 3.4 percent. In addition to growth expansion in the United States, the United Kingdom, as well modest recovery in the Euro zone countries, global growth will continue to be driven by growth in developing countries, expected to be between 5.3 to 5.5 percent in 2014 and 2015 respectively, led by China and India. Higher global demand is expected to boost MENA energy and manufactured exports in countries that have trade linkages with high-income countries. MENA countries share many structural problems that have prevented economies from moving to a higher, sustainable growth path. Fiscal spending in almost all MENA countries is dominated by a large civil-service wage bill and general subsidies. The global recovery remains fragile and downside risks, including continued low inflation in high-income economies, can weaken demand and delay economic recovery.